Budget Impact Analysis of the Change in Peritoneal Dialysis Use Rate in Korea. Issue 6 (November 2019) - Kim, Jimin; Lee, Na Rae; Son, Soo Kyung; Lee, Jung Pyo; Park, Jung Tak; Kim, Yun Jung; Ryu, Dong-Ryeol
Background: While the number of peritoneal dialysis (PD) patients has decreased by 14.4% from 2006 to 2016, the number of hemodialysis (HD) patients has sharply increased, by 237.2%, in the same period, leading to an increase in the total medical cost. We analyzed the effects of the changes in PD use rates for dialysis patients in Korea on the healthcare budget using budget impact analysis (BIA). Methods: The analysis modeled the influence of the increase in dialysis for the target population, changes in modality use rate, and/or changes in costs per patient-year on total medical cost for patients on dialysis, using the National Health Insurance Service (NHI) claims data. We developed 8 scenarios according to the changing PD use rate. Results: In scenarios 1 – 4 (increase in PD patients by 6%, 13%, 20%, and 50% of non-diabetic prevalent HD patients under 65), 5-year budget savings ranged from $47 million to $394 million (0.9% – 7.3% of the end-stage renal disease [ESRD] budget). In scenarios 5 – 8 (increase in incident PD patients by 20%, 50%, 70%, and 100% of non-diabetic patients under 65), 5-year savings ranged from $25 million to $74 million (0.5% – 1.4% of the ESRD budget). In all scenarios, budget savings were higher as PD patients increased, showing a gradually growing trend. Conclusion: In all scenarios from the payer's perspective, savings could be achieved through an increase in PD use. Selecting PD for ESRD patients without different expected clinical outcomes between HD and PD would be beneficial to the NHI budget.